2022
DOI: 10.1002/hbm.26116
|View full text |Cite
|
Sign up to set email alerts
|

Self‐deception: Distorted metacognitive process in ambiguous contexts

Abstract: As one of the commonly used folk psychological concepts, self‐deception has been intensively discussed yet is short of solid ground from cognitive neuroscience. Self‐deception is a biased cognitive process of information to obtain or maintain a false belief that could be both self‐enhancing or self‐diminishing. Study 1 ( N = 152) captured self‐deception by adopting a modified numerical discrimination task that provided cheating opportunities, quantifying errors in predicting future perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 112 publications
0
4
0
Order By: Relevance
“…Other authors emphasize its function as an avoidance strategy, such as avoiding distress (Fingarette, 1969;Sackeim, 1983). It has also been proposed that self-deception may arise from selective attention, whereby certain information is ignored or dismissed, despite evidence (Greenwald, 1997;Sharot, 2011), Other research suggests that self-deception is a cognitive process of biasing information to obtain or maintain a false belief that may be beneficial or detrimental to oneself (Mei et al, 2022). A close relationship has been found between self-deception and deception of others (Lu and Chang, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Other authors emphasize its function as an avoidance strategy, such as avoiding distress (Fingarette, 1969;Sackeim, 1983). It has also been proposed that self-deception may arise from selective attention, whereby certain information is ignored or dismissed, despite evidence (Greenwald, 1997;Sharot, 2011), Other research suggests that self-deception is a cognitive process of biasing information to obtain or maintain a false belief that may be beneficial or detrimental to oneself (Mei et al, 2022). A close relationship has been found between self-deception and deception of others (Lu and Chang, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Twenty Chinese‐speaking undergraduates at the Chinese University of Hong Kong participated after giving informed consent. The number of participants was determined in accordance with a power analysis using the G*Power software (Erdfelder et al., 1996), which indicated that a sample of 18 participants was needed to detect differences with a repeated measures ANOVA with power (1 − β ) set at 0.80, alpha at 0.05, and an estimated ŋ p 2 of 0.06 (medium) (Cohen, 1988; Mei et al., 2023; Wang et al., 2021). They were all right‐handed, had normal or corrected‐to‐normal vision and normal hearing, and were not diagnosed with any psychiatric or neurological disorders.…”
Section: Methodsmentioning
confidence: 99%
“…The number of participants was determined with a power analysis using the G*Power software (Erdfelder et al., 1996), indicating that a sample of 18 participants was needed to detect differences with a repeated measures ANOVA with power (1 − β ) set at 0.80, alpha at 0.05, and an estimated ŋ p 2 of 0.06, a medium effect size by Cohen's (1988) standard. The selection of a medium effect size was based on its use in previous ERP studies on false belief processing (e.g., Mei et al., 2023; Wang et al., 2021). They were right‐handed, had normal hearing, and normal or corrected‐to‐normal vision with no history of psychiatric or neurological disorders.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation